Therapeutic Effectiveness of Cefoperazone for Community-Acquired Pneumonia and Associated Factors in a Tertiary Care Hospital, Vietnam - Le, Cua Ngoc; Nguyen, Duong Trung; Kaewsawat, Supreecha; Suwangbamrung, Charuai; Khammaneechan, Patthanasak (Journal of Pharmacy and Nutrition Sciences, 2021)
Purpose: This study aimed to (i) identify the pathogenic bacterial profile and Cefoperazone (CPZ) sensitivity; (ii) assess the therapeutic effectiveness of CPZ and (iii) determine factors associating with the treatment success. Patients and methods: The retrospective study was conducted in Kien Giang hospital, Vietnam. Sample size was 210 medical records of community-acquired pneumonia (CAP) patients admitted to the hospital from January to December 2018. The Chi square and Fisher’s exact test were used to determine factors associating with the treatment success such as age, gender, comorbidities, levels of CAP severity respiratory rate, PaO2, and laboratory findings of blood tests. Statistical significance was at level α = 0.05. Results: The main pathogenic bacteria were Klebsiella pneumoniae (29.1%), Streptococcus pneumoniae (26.7%) and Pseudomonas aeruginosa (14%), and were highly susceptible to CPZ. Mean duration of obtaining clinical stability was 3.01 days. The obtainment of clinical stability through CPZ monotherapy on the third, fifth and seventh day of treatment process accounted for 78.9%, 87.6% and 100% of total cases, respectively. CPZ achieved a highly successful rate in the monotherapy (79.07%) if the treatment was guided by antibiotic sensitivity testing results. The association between the treatment success and factors such as age, respiratory rate, and severity category of CAP were statistically significant (p<0.05). Conclusion: Minimizing CPZ resistance, and CPZ overuse during CAP therapy is necessary. The factors associating with the success of therapy are useful in predicting the prognosis of CAP patients, planning the sequential therapy, and determining hospital discharge.